Peningkatan Motivasi Belajar Siswa Dalam Pembelajaran IPA Menggunakan Metode Quantum Theaching Learning Kelas V SDI Bukaan - Mega Dwi Susanti (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
This research was conducted at SDI Opening with class V research subjects with a total of 52 students. This research is a type of classroom action assessment, a learning method used by Quantum Teaching Learning. The study was conducted in 2 cycles. The steps used in this study are by pretesting to find out the initial ability of students, then the provision of the material taught, after which students conduct discussion activities in groups. The next stage is posttest, to find out the understanding and learning achievements that students have achieved.